Moneygrams: Recalled Childhood Memories about Money and Adult Money Pathology - Adrian Furnham; Sophie von Stumm; Rebecca Milner (Journal of Financial Therapy, 2014)
In this study 512 adults completed two questionnaires. One questionnaire was devised specifically for this study concerning childhood memories of parental beliefs and behaviours with respect to money (i.e moneygrams)/ The second questionnaire established a measure of “money pathology” (Forman, 1987). The moneygram questionnaire was based on clinical cases and idiographic studies on money pathology. Around a fifth of the items showed significant sex differences. Factor analysis highlighted one clear factor, namely “money secrecy” - which was associated with greater levels of spending money pathology in adulthood. In women, but not in men, higher family money secrecy was significantly associated with compensating and hoarding money pathologies. The latter two were not related to income in either men or women. Implications and limitations of these results are considered.
Keywords: Childhood; money; parents; emotional association; gender; money behaviors